2007
DOI: 10.1038/sj.jhh.1002247
|View full text |Cite
|
Sign up to set email alerts
|

Circulating homocysteine and large arterial stiffness and thickness in a population-based sample of middle-aged and elderly men

Abstract: Elevated plasma homocysteine (tHcy) is considered as a risk factor for cardiovascular events, and has been associated with arterial stiffness and subclinical atherosclerosis in subjects with classical cardiovascular risk factors. The aim of this study is to investigate the association of plasma tHcy with functional and structural changes in the large arteries by measuring aortic pulsewave velocity (PWV) and carotid artery intima-media thickness (CIMT). In a population-based sample of 376 middle-aged and elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…In patients with Type 2 diabetes (T2DM) with and without nephropathy, and in elderly men with cardiovascular risk factors including diabetes, mean tHcy levels were not significantly correlated with common carotid IMT [15], [32], [33] and [34]. On the other hand, significant cross-sectional associations of IMT with higher (> 9-12 μmol/L) versus lower levels of tHcy have been reported by The National Heart, Lung, and Blood Institute (NHLBI) Family Heart Study in older subjects (n=1467) with and without diabetes mellitus [14].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with Type 2 diabetes (T2DM) with and without nephropathy, and in elderly men with cardiovascular risk factors including diabetes, mean tHcy levels were not significantly correlated with common carotid IMT [15], [32], [33] and [34]. On the other hand, significant cross-sectional associations of IMT with higher (> 9-12 μmol/L) versus lower levels of tHcy have been reported by The National Heart, Lung, and Blood Institute (NHLBI) Family Heart Study in older subjects (n=1467) with and without diabetes mellitus [14].…”
Section: Discussionmentioning
confidence: 99%
“…The subjects and methods of recruitment of this study have been described elsewhere. [8][9][10] The subjects were recruited by asking women participating in other studies conducted by the department by letter whether they possibly knew interested men between ages 40 and 80. Invitation letters were sent to 770 participating women.…”
Section: Methodsmentioning
confidence: 99%
“…We reviewed the findings of seven cross-sectional studies and one cohort study to investigate the association between Hcy levels and arterial stiffness using PWV or CAVI as a quantitative marker for the degree of early arteriosclerosis (Supplemental Table 1). The cross-sectional studies reported inconsistent results, with no association found in three studies [16][17][18] and a Dummy variables (0 and 1) were used for the 5-year CAVI values ( 9.0 and ≥ 9.0) and for the 5-year change in the CAVI values ( 0.48 and ≥ 0.48). Univariate analysis that was adjusted for age.…”
Section: Discussionmentioning
confidence: 98%
“…Among patients with hypertension, most studies have investigated the association between high Hcy levels and arterial stiffness by measuring PWV 14,15) . In addition, studies among the general population include seven cross-sectional studies and one cohort study [16][17][18][19][20][21][22][23] . However, the findings of these studies were inconsistent.…”
Section: Introductionmentioning
confidence: 99%